Active controlled motion in early rehabilitation improves outcome after ankle fractures: a randomized controlled trial. (March 2018) - Jansen, Hendrik; Jordan, Martin; Frey, Sönke; Hölscher-Doht, Stefanie; Meffert, Rainer; Heintel, Timo
Objective: To evaluate the use of active controlled motion (ACM) after unstable ankle fractures needing initial partial weight-bearing. Design: Prospective randomized controlled trial. Setting: Inpatient and outpatient clinic. Subjects: A total of 50 patients with unstable ankle fractures and the need for partial weight-bearing for six weeks. Interventions: Randomization in two groups: physiotherapy alone or physiotherapy with an additional ACM device. Main measures: Follow-up after 6 and 12 weeks. Range of motion, visual analogue scale for foot and ankle (VAS FA), Philip score, Mazur score, American Orthopaedic Foot & Ankle Society (AOFAS) score and dynamic pedobarography. Results: Range of motion was better in the ACM group at six weeks (mean 49° ± 11.1° vs. 41.3° ± 8.1°). Questionnaires revealed better outcome after six weeks in the VAS FA (56 ± 13.7 vs. 40.6 ± 10.5), Mazur score (64.4 ± 12.3 vs. 56.7 ± 11) and AOFAS score (71.2 ± 12 vs. 63.6 ± 8.7) ( P > 0.02 for all). Better outcome after 12 weeks in all questionnaires (VAS FA, 77.7 ± 13.8 vs. 61.4 ± 16.3; Philip score, 79.1 ± 10.9 vs. 60.1 ± 21.7; Mazur score, 83.9 ± 10.7 vs. 73.1 ± 14.1; AOFAS score, 87.5 ± 7.9 vs. 75.2 ± 11.7) ( P < 0.01 for all). Pressure balance was better under the midfoot region after 12 weeks in the ACM group (Δ P 4.4 N vs. 34.0 N; P = 0.01). The ACM group had an earlier return to work after 10.5 (range, 3–17) versus 14.7 (range, 9–26) weeks ( P = 0.02). Conclusion: The use of ACM for patients needing initial partial weight-bearing after operatively treated unstable ankle fractures in the first six postoperative weeks leads to better clinical and functional results and an earlier return to work.